Penerapan Prosedur Vouching dan Konfirmasi Dalam Audit Investigatif Atas Akun Beban Gaji (Studi Kasus Pada PT X) - Novi Eka Nadias; Gideon Setyo Budiwitjaksono (Jurnal Riset Akuntansi, 2024)
Investigative audit can be interpreted as a process carried out by an independent party to prove the presence or absence of fraud. Seeing these conditions, the investigative auditor must carry out audit procedures effectively and efficiently in order to obtain conclusions regarding how fraud can occur. It is undeniable that various forms of fraud can occur in every company, one of which is fraud in the employee payroll system. Furthermore, PT X is a manufacturing company and one of the clients of KAP Y which requires investigative audit services to detect fraud in the payment of salaries for casual employees. The purpose of this research is to analyze the application of vouching and confirmation procedures in the investigative audit process of the salary expense account at PT X. The writing of this article uses a qualitative approach based on case studies. Secondary data for this research was obtained through interviews and documentation. Data analysis was carried out by preparing questions and recording the results of interviews for further analysis. The author also organizes the information obtained to get a conclusion. The results of this study prove that vouching and confirmation procedures are able to detect fraud in the investigative audit process. In this case, it has been found that there is a difference between the amount of funds spent by the company for salary payments and the amount of funds received by daily casual employees.